Strategic management concepts a competitive advantage approach - David, Fred R.; David, Forest R. (Pearson Education, 2015)
In today's economy, gaining and sustaining a competitive advantage is harder than ever. This edition includes 29 new cases and end-of- chapter material, including added exercises and review questions.